Adjunctive Corticosteroids for Pediatric Parapneumonic Effusion and Empyema: A Systematic Review and Meta-Analysis of Randomized Trials - Bagus Ananta Yuktasya, Putu; Pradnya Dewanti, Nia; Ashhabul Kahfi Mathar, Muhammad (Jurnal Indonesia Sosial Sains, 2025)
Parapneumonic effusion and empyema are significant causes of morbidity in pediatric pneumonia, driven by an intense pleural inflammatory response. While corticosteroids have been suggested to modulate this inflammation and speed up recovery, evidence regarding their use in pleural complications in children remains limited. This study aims to assess the efficacy of adjunctive corticosteroid therapy in improving clinical outcomes among children hospitalized with parapneumonic effusion or empyema. A systematic search of PubMed, Cochrane Library, and ScienceDirect was conducted from inception to November 2025. Eligible studies included randomized or comparative cohort designs evaluating systemic or intrapleural corticosteroids alongside standard care in pediatric parapneumonic effusion. The primary outcome was length of hospital stay. Three randomized trials were included in the quantitative synthesis, and one observational cohort was analyzed qualitatively. A fixed-effect model was used due to minimal heterogeneity. Among 167 randomized participants, adjunctive corticosteroid therapy significantly reduced hospital stay (mean difference –2.96 days; 95% CI –4.57 to –1.36). Qualitative analysis showed consistent improvements in fever resolution, radiologic recovery, and inflammatory markers, especially when corticosteroids were given early. The observational cohort with delayed rescue steroids showed no improvement, emphasizing the importance of timing. These findings support early corticosteroid use, consistent with the pathophysiology of pleural inflammation. While variations in steroid regimens and sample sizes should be considered, the consistent benefits strengthen the evidence. Early corticosteroid therapy accelerates recovery and shortens hospitalization in pediatric parapneumonic effusion or empyema, making it a safe and effective complement to standard care.​